An assessment of the validity and reliability of the P022–P version of e-Celsius core temperature capsules. (February 2023) - Service, Thomas W.; Junker, Katerina; Service, Breanna; Coehoorn, Cory J.; Harrington, Marisa; Martin, Steven; Stuart-Hill, Lynneth A.
Abstract: Core temperature monitoring is a research tool used in many studies, though most popularly, heat strain. Ingestible core temperature capsules are a non-invasive and increasingly popular choice for measuring core body temperature, particularly considering the well-established validation of capsule systems. A newer version of the e-Celsius ingestible core temperature capsule has been released since the preceding validation study resulting in a paucity of validated research for the current version of capsules, P022–P, used by researchers. Using a 1:1 ratio of propylene glycol to water in a circulating water bath, and a reference thermometer with resolution and uncertainty of 0.01 °C, we assessed the validity and reliability of 24 P022–P e-Celsius capsules in three groups of eight, at seven temperature plateaus between 35 °C, and 42 °C in a test-retest format. The systematic bias of these capsules across all 3360 measurements was found to be −0.038 °C ± 0.086 °C (p < .001), The TEST-RETEST evaluation revealed excellent reliability by way of a minute overall mean difference of 0.0095 °C ± 0.048 °C (p < .001), and an intraclass correlation coefficient of 1.00 for each of TEST and RETEST conditions. Although quite small, differences in systematic bias across temperature plateaus were observed for both the OVERALL bias—between 0.00066 °C and 0.041°C—and TEST/RETEST bias—between 0.00010 °C and 0.016 °C. We found that the new capsule version outperforms manufacturer guarantees, with half of the systematic bias observed in a validation study of the previous capsule version. Though these capsules tend to slightly underestimate temperature, we find they possess excellent validity and reliability between 35 °C and 42 °C. Highlights: There is a mean bias of −0.038C for the P022–P e-Celsius capsule version. GI capsule accuracy and precision has substantially improved in recent years. GI capsules show exceptional reliability, but may be challenged by fluid ingestion. Improved accuracy and precision of GI thermometry may entice further use.